Analysis of Ability to Prepare Learning Evaluation Minimum Competency Assessment (AKM) during the Covid 19 Pandemic at SD Negeri 3 Abepura, Jayapura City - Ali Aisyah; Yuliana S. Chelsi; Ristiani Ria (PT FORMOSA CENDEKIA GLOBAL, 2023)
This research was conducted at SD Negeri 3 Abepura to analyze the ability to prepare a Minimum Competency Assessment (AKM) Learning Evaluation during the Covid 19 Pandemic. The method used in this research is qualitative, collecting information through interviews and observing the situation in elementary schools, as well as through documentary research. The results of this study indicate that in carrying out the AKM at SD Negeri 3 Abepura it is done online with questions developed by the Directorate of Basic Education, Ministry of Education and Culture. SD Negeri 3 Abepura teachers have received socialization related to AKM. However, they have not received technical assistance regarding the preparation of questions, so the teacher has never prepared AKM questions. As a recommendation, teacher readiness in dealing with AKM is very important, therefore teachers can collaborate at their respective class levels in carrying out student-based learning plans, including it is important for teachers to increase teacher community forums available online to share experiences and practical.